Letter (copy) : Position in the Basque Country - Tewson, Vincent
012b-0029-001 Secretary's. HVT/EK/1330. 10th July, 1939 Senor J. I. de Lizaso, Basque Delegation, 14, Eccleston Square, London, S.W.1. Dear Senor Lizaso, Position in the Basque Country. I have your letter of the 7th July giving further information in regard to the position in the Basque country, for which I am greatly obliged. Yours sincerely, Assistant Secretary. 292/946/12b/29